Ensuring an effective system of the sanitary condition of restaurant establishments under the HACCP - Borysova, Evelina; Osadcha, Veronika; Fefelov, Denys; Kuzmin, Oleg (My University, 2023)
У статті розглядаються виклики, пов’язані з контролем критичних точок у закладах ресторанного господарства, з метою зниження ризиків контамінації харчових продуктів, забезпечення безпеки на робочих місцях та загального благополуччя підприємства

This article addresses the challenges associated with controlling critical points in a food service enterprise to mitigate the risks of food contamination and ensure workplace safety and overall enterprise well-being
Keywords: кафедра технології ресторанної і аюрведичної продукції; HACCP; контамінація харчових продуктів; contamination